Pengaruh Harga, Produk dan Tempat Terhadap Minat Beli Pelanggan - Muhammad Mashudi Azrullah; Khamdan Suriyok (Ecobuss, 2022)
The research was conducted with the aim of analyzing and explaining the effect of price, product and place on customer buying interest. The research was conducted at SME Chicken Shilin in Yadika Bangil Village - Pasuruan. Data were collected through observation, document analysis, and distributing questionnaires. The method of data analysis was carried out with a descriptive quantitative method using multiple regression analysis tools with the help of the SPSS program. The results of the study show that first, the variables of price, product and place have a simultaneous effect on customer buying interest. Second, the price variable has a partial effect on customer buying interest. Third, the product variable has a partial effect on customer buying interest. Fourth, the place variable has an effect on customer buying interest, the place variable has the most dominant influence on customer buying interest. Keywords : Price, Product, Promotion, SME